Chinese herbal medicine for premature ovarian insufficiency: A protocol for systematic review - Shao, Yifeng (Medicine (Baltimore), 2020)
BACKGROUND: Premature ovarian insufficiency (POI) is the loss of function of the ovaries before age 40. Chinese herbal medicine (CHM) has been treating POI for long time. Therefore, we conduct this study to assess the efficacy and safety of CHM for POI. METHODS: Seven databases will be searched from inception to December 31, 2018: PubMed, Embase, Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), China Biology Medicine disc (CBM), WanFang Database, and Chongqing Chinese Scientific Journal Database (CQVIP). Randomized controlled trials that used CHM will be included. Two reviewers will independently complete the study selection, data extraction, and study quality assessment according to Cochrane Collaboration. All the data will be analyzed using Review Manage 5.3 software. RESULTS: This study will generate a comprehensive summary on effectiveness and safety of CHM for POI. CONCLUSION: This study may be beneficial to health policymakers, clinicians, and patients with regard to the use of CHM in POI treatment. TRIAL REGISTRATION NUMBER: PROSPERO CRD 42019144629.